Metafora w służbie polityki. Aleksander Kwaśniewski o wstąpieniu Polski do NATO i akcesji do Unii Europejskiej - Wołoszyn , Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The aim of the article is to analyse selected metaphors used by the President of the Republic of Poland, Aleksander Kwaśniewski, in public appearances during his presidency in from 1995 to 2005. The subject of interest are public appearances in which A. Kwaśniewski talked about the preparation and accession of Poland to one of the most prestigious organisations in the world – the North Atlantic Alliance (NATO) in 1999 and the European Union (EU) in 2004. The author analyses selected metaphors (including: HOME, ROAD, FAMILY), regarding Poland’s accession to these structures, which were used by the president in his speeches. The author discusses how A. Kwaśniewski, who was then the head of state, used metaphors to present his attitude towards the issue of Poland’s integration with North Atlantic Alliance and accession to the European Union and what vision of Poland’s presence in these structures he had.